Penentuan Variabel dan Indikator Outcome Jaringan Irigasi di Daerah Irigasi Batang Anai Sumatera Barat dengan Teknik Delphi - Widiyanto, Wirawan (Jurnal Sosial Ekonomi Pekerjaan Umum, 2013)
Bureaucratic reform urges ministries to increase the performance of their strategic plan to meet their targets. The outcomes must then be adopted. Irrigation system is one of the infrastuctures which should have significant outcomes. Batang Anai irrigation system in West Sumatera is the widest irrigation system which produces significant outcomes. The aim of the research was to determine variabels and indicators of outcomes using Delphi method for Batang Anai irigation system. Delphi method was carried out through Focus Group Discussion to obtain 5 variabels and 11 indicators of outcomes. The results showed that the most important variabels were the extent of water fulfillment for the farmers and coverage area of irrigation. The two variabels represent Batang Anai irrigation system performance.